2009
DOI: 10.1111/j.1600-0404.1984.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the incidence of multiple sclerosis in Western Norway

Abstract: – In the county of Hordaland, Western Norway, the prevalence of MS has been shown to have increased from 20/100,000 in 1963 to 60/100,000 in 1983. This study shows that the increase in prevalence was caused by a highly significant and marked increase in incidence over a 30‐year period. The average annual incidence of about 2 per 100,000 population in 1953–1962 increased to 4 per 100,000 in the period 1968–1977. The rise in incidence was parallel for both sexes until 1970. In the last 10 years, the incidence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, the time delay between onset and diagnosis is decreasing and consequently, the methodological issue of underestimated prevalence will probably be reduced in future studies. The incidence of MS in Hordaland County has in previous studies increased from 0.2/100 000 in 1935, 17 to 0.67/100 000 in 1951 18 and to 4.7/100 000 in 1978-1982. 19 However, in the present long-term follow-up study, we also identified patients with disease onset years prior and thus higher incidence rates of 1.8/100 000 during 1953-1957, 6.9/100 000 during 1978-1982 followed by a stable high level of approximately 7-8/100 000 during later years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time delay between onset and diagnosis is decreasing and consequently, the methodological issue of underestimated prevalence will probably be reduced in future studies. The incidence of MS in Hordaland County has in previous studies increased from 0.2/100 000 in 1935, 17 to 0.67/100 000 in 1951 18 and to 4.7/100 000 in 1978-1982. 19 However, in the present long-term follow-up study, we also identified patients with disease onset years prior and thus higher incidence rates of 1.8/100 000 during 1953-1957, 6.9/100 000 during 1978-1982 followed by a stable high level of approximately 7-8/100 000 during later years.…”
Section: Discussionmentioning
confidence: 99%
“…Some regions have reported increased incidence [e.g. [20][21][22][23][24] whereas others have shown no change or decreased incidence [e.g. 25,26].…”
Section: Sex Ratio and The Increasing Prevalence Of Msmentioning
confidence: 99%
“…In many regions around the world the incidence of multiple sclerosis (MS) appears to be rising 1 2 3 4 5 6 7 8 9 10 11 12 13. Although this had been widely ascribed to improved ascertainment, studies in Canada showed this was a real increase;14 year of birth (YOB) was a significant predictor of sex ratio over more than five decades (p<1.0 −28 ).…”
mentioning
confidence: 99%